Strengthening Digital Literacy and Branding In The MSME and Disability Community In Cimareme Village - Salma, Anisa; Nizami, Lulu Ulfa; Mote, Anton; Jaya, Rama Chandra; Ramdan, Ahmad Taufiq Maulana; Gunawan, Syam; Wiryany, Detya (Inaba of Community Services Journal, 2025)
This community service program aims to strengthen the digital communication, marketing, and microfinance management skills of MSME actors and people with disabilities in Cimareme Village, West Bandung. Although digital technology offers wide opportunities for business development, local entrepreneurs particularly the VirageAwie community still face limitations in digital literacy, branding, public communication, and simple financial recording. Using a Focus Group Discussion (FGD) method with a participatory approach, the program identified partners’ needs and designed thematic training covering digital marketing strategies, branding and public speaking, and digital market access. All sessions utilized experiential learning to promote hands-on practice in creating digital promotional content, delivering product presentations. The program also assisted in developing the VirageAwie website as a digital branding tool to expand market reach. The results show improvements in participants’ understanding of digital communication strategies, confidence in marketing interactions, ability to utilize social media. This empowerment initiative demonstrates the effectiveness of participatory communication and practical training in enhancing the independence and competitiveness of local entrepreneurs. Follow-up programs are recommended to ensure sustainable development, including SEO optimization, cross-cultural communication.